Bank Performance and Stock Returns: An Analysis of Conventional and Islamic Banks in Indonesia - Wibien, Jemima Donna; Yusup, Adi Kurniawan (Oikonomia: Jurnal Manajemen, 2025)
Purpose This research focuses on financial ratios and the differences between conventional and Islamic banks to understand their impact on stock returns. The purpose of this research is to identify the key factors causing affecting the stock price for banks listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023.. Methodology This study uses a quantitative approach, analyzing data from 37 banks' annual reports (222 firm-year observations). The Generalized Method of Moments (GMM) using STATA 17 was applied to ensure accurate results. Findings Findings show that NPL and ROE negatively impact stock returns, while CAR and LDR have no influence. On the other hand, Islamic banks' liquidity management, measured by ROE and LDR showed a more positive effect on stock returns compared to conventional banks. Suggestion Future studies should consider including broader factors like economic conditions. This study's limitation lies in its focus on financial ratios without factoring in macroeconomic factors.